Dampak Pembelajaran Daring di Era Pandemi Covid-19 terhadap Kompetensi Numerasi Siswa Sekolah Dasar - Fauzi, Irfan; Fhilrizki, Salma Ihsani (Jurnal Didaktika Pendidikan Dasar, 2022)
The purpose of this research was to find out the impact of online learning in students' numeracy skills in addition and subtraction of fractions in grade 5 elementary school. This research used a quantitative approach with a pre-experimental method, and the treatment is an online learning system. The data collection technique used tests. The test given is the students' numeracy skills in addition and subtraction of fractions in grade 5 elementary school. Data analysis in this research used descriptive statistics (N-Gain) and the mean difference test (Mann-Whitney) used the SPSS Statistics 22 application. The results of this research indicate that the student's N-Gain score is 0.39. This indicates that there is an increase in numeracy scores in the moderate category, and based on the average difference test, sig. which is 0.002 smaller than 0.05 (α). Its means there is a significant increase in students' numeracy skills using online learning.Keywords: Online Learning, Numeracy, Addition and Subtraction of Fractions